Improving the seaport service quality by implementing digital technologies - Agatić, Adrijana (Array, 2020)
The process of digitalization i.e. implementation of digital technologies is widely present in the seaports. Digitalization encourages seaports to adjust and implement digital technologies in providing their services, while constantly striving to stay efficient, profitable and competitive. The implementation of digital technologies results in altered perspective of seaport service quality. Since seaport service quality is not prescribed and strictly defined, the importance of digitalization should be taken into consideration, which includes redefining the seaport service quality factors. Worlds’ leading seaports, especially leading European seaports, recognized the possibilities of digital technologies in providing quality seaport services and are investing in their implementation. In this paper, seaport service quality is analysed in the context of digitalization i.e. the implementation of digital technologies. The purpose of this paper is to define the quality factors and opportunities for improving seaport service quality based on the analysis of digital technologies implemented in seaports.